Pencatatan Pernikahan Beda Agama Perspektif Undang-Undang Nomor 23 Tahun 2006 (Study Putusan Nomor 12/Pdt.P/2022/PN.Ptk) - Ali, Umar; Efendi, Rahmad (Universitas Ekasakti, 2023)
Indonesia is a unitary country consisting of thousands of large and small islands, and consisting of various tribes, cultures and religions, and has the motto Bhinneka Tunggal Ika. Interaction between tribes, races and religions is the initial door for people to know each other so that from this interaction there is who progress to the stage of marriage, there are even those who get married even though they are hampered by differences in religion. It is feared that this will gradually cause problems, if we refer to existing religious norms regarding certain boundaries regarding marriage. This resulted in a decision by the Pontianak District Court Number 12/Pdt.P/2022/PN.Ptk. who granted the request to carry out the registration of interfaith marriages. This determination certainly attracts attention if you remember the rules contained in Law No. 1 of 1974 that a marriage is valid if it is carried out according to the laws of each religious belief. Even though registration has been regulated in Article 35 Letter (a) of Law Number 23 of 2006 in conjunction with Law Number 24 of 2013 concerning Population Administration, the regulations regarding interfaith marriages in the Marriage Law still experience a legal vacuum. It is hoped that this article can provide insight to the public regarding the problems of implementing interfaith marriages in Indonesia.